(untitled) (Asian-Australasian Journal of Food Safety and Security, 2023)
The present study was conducted to determine the pre harvest interval of chlorpyrifos and quinalphos in hyacinth bean in the agro-climatic condition of Bangladesh to ensure safe food for the consumers. A supervised field trial was undertaken in the experimental field of Entomology Division of BARI, Gazipur and the selected pesticides (chlorpyrifos and quinalphos) were sprayed with the recommended dose (1.5 ml/L of water). The samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 and 12 days after spray (DAS). The collected samples were extracted and cleaned up using modified Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and the residues were determined by Gas Chromatography (GC) coupled with Flame Thermionic Detector (FTD). The residue of chlorpyrifos was detected upto 8 DAS (0.027 mg/Kg) at a level above the EU-MRL, and at 9 DAS, no residue was detected. So, the PHI for chlorpyrifos was set at 9 DAS. On the other hand, the residue of quinalphos was detected upto 9 DAS, of which the level of residue was above EU-MRL upto 8 DAS (0.02 mg/kg). At 9 DAS, the quinalphos residue remained 0.009 mg/Kg, which was below EU-MRL. So, the PHI for quinalphos was set at 9 DAS. Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 47-55